Association between dietary nutrient intake and prevalence of myopia in Korean adolescents: evidence from the 7th Korea National Health and Nutrition Examination Survey - Kim, Jeong-Mee; Choi, Yean Jung (Frontiers in Pediatrics, 2024)
The rise in myopia prevalence, particularly among adolescents in East Asia, is a cause for concern. While a combination of environmental and genetic factors is understood to contribute to this trend, the role of dietary nutrients is not yet fully clarified.Objective: To assess the potential association between the intake of specific nutrients and the prevalence of myopia in a large, population-based sample of Korean adolescents.Methods: Data from 18,077 adolescents (average age: 15.05 ± 1.67 years; 51.7% male, 48.3% female) who participated in the 7th Korea National Health and Nutrition Examination Survey (KNHANES VII, 2016) were analyzed. Refractive error was measured using an auto-refractor-keratometer (KR-8800) -2 -without cycloplegia. Dietary intake of 14 nutrients was assessed through a 24-hour personalized dietary recall method.The study revealed a myopia prevalence of 87.6% among the adolescents. Multivariable models adjusted for age, gender, BMI, and other confounding factors indicated that higher intakes of carbohydrates, proteins, cholesterol, sodium, and vitamin B2 were associated with an increased risk of myopia. Conversely, higher intake of vitamin C was found to be associated with a decreased risk.The findings suggested a potential association between dietary nutrient intake and myopia prevalence in Korean adolescents. While the study did not establish a causal link, the differences in nutrient intake between the myopic and non-myopic groups could indicate that diet plays a role in the development or progression of myopia. Further research is warranted to corroborate these findings and explore the underlying mechanisms.